Laser Welding and Syncristallization Techniques Comparison: In Vitro Study - C. Fornaini; E. Merigo; P. Vescovi; M. Meleti; S. Nammour (International Journal of Dentistry)
Background. Laser welding was first reported in 1967 and for many years it has been used in dental laboratories with several advantages versus the conventional technique. Authors described, in previous works, the possibility of using also chair-side Nd : YAG laser device (Fotona Fidelis III, 𝜆=1064 nm) for welding metallic parts of prosthetic appliances directly in the dental office, extra- and also intra-orally. Syncristallisation is a soldering technique based on the creation of an electric arc between two electrodes and used to connect implants to bars intra-orally. Aim. The aim of this study was to compare two different laser welding devices with a soldering machine, all of these used in prosthetic dentistry. Material and Methods. In-lab Nd : YAG laser welding (group A = 12 samples), chair-side Nd : YAG laser welding (group B = 12 samples), and electrowelder (group C = 12 samples) were used. The tests were performed on 36 CrCoMo plates and the analysis consisted in evaluation, by microscopic observation, of the number of fissures in welded areas of groups A and B and in measurement of the welding strength in all the groups. The results were statistically analysed by means of one-way ANOVA and Tukey-Kramer multiple comparison tests. Results. The means and standard deviations for the number of fissures in welded areas were 8.12±2.59 for group A and 5.20±1.38 for group B. The difference was statistical significant (𝑃=0.0023 at the level 95%). On the other hand, the means and standard deviations for the traction tests were 1185.50±288.56 N for group A, 896.41±120.84 N for group B, and 283.58±84.98 N for group C. The difference was statistical significant (𝑃=0.01 at the level 95%). Conclusion. The joint obtained by welding devices had a significant higher strength compared with that obtained by the electrowelder, and the comparison between the two laser devices used demonstrated that the chair-side Nd : YAG, even giving a lower strength to the joints, produced the lowest number of fissures in the welded area.